Engaging in International Projects and Foreign Exchange Programs During and After the Pandemic: Insights and Practices - Karki, Sujeet; Neupane, Bharat Prasad; Sapkota, Rajesh (Generasi Sains Indonesia, 2024)
This is an autoethnographic research that examines the advantages of participating in international projects and foreign exchange programs during the COVID-19 pandemic and beyond. These activities are perceived as professional practices which allow teachers to contribute to the development of learners, intercultural awareness, and global cooperation via online tools through the application of autoethnography as the methodology. The personal narratives were used to generate data, and the data were gathered in the form of screenshots and thematic analysis based on the framework created by Gibbs (2008). The results indicate that involvement in international projects substantially professionalized teachers by enhancing 21 st -century competencies, including critical thinking, collaboration, communication, creativity, digital literacy, and intercultural awareness. The engagements also contributed to creating networks across the globe, enhancing rapport with colleagues and learners around the world, and transforming the practice of teaching throughout and after the pandemic. To sum up, international partnerships and foreign exchange programs do not only play a vital role in the professional development of teachers, but also enable learners to generate confidence, master languages, and experience cultural diversity. The paper brings out the possibilities of technology-mediated global initiatives as sustainable practices in improving teacher identity and advancing education during and after a crisis.